2023
DOI: 10.1186/s41182-023-00516-w
|View full text |Cite
|
Sign up to set email alerts
|

Malaria vaccines: the 60-year journey of hope and final success—lessons learned and future prospects

Abstract: Background The world has made great strides towards beating malaria, although about half of the world population is still exposed to the risk of contracting malaria. Developing an effective malaria vaccine was a huge challenge for medical science. In 2021 the World Health Organization (WHO) approved the first malaria vaccine, RTS,S/AS01 vaccine (Mosquirix™), for widespread use. Main abstract body This review highlights the history of development, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 135 publications
0
17
0
Order By: Relevance
“…Some strategies concentrate on the sporozoite and/or liver phases of the life cycle (pre-erythrocytic phases), while others focus on the asexual and the sexual erythrocytic as well as mosquito stages. [65]…”
Section: Trypanosoma Cruzimentioning
confidence: 99%
“…Some strategies concentrate on the sporozoite and/or liver phases of the life cycle (pre-erythrocytic phases), while others focus on the asexual and the sexual erythrocytic as well as mosquito stages. [65]…”
Section: Trypanosoma Cruzimentioning
confidence: 99%
“…Indeed, even malaria vaccines have been in R&D for at least eight decades. Since at least the 1940s, researchers have been attempting to induce protective immunity to malaria parasites using, e.g., killed or inactivated sporozoites, before RTS,S and R21 (that target the Plasmodium falciparum circumsporozoite protein and, to a lesser extent, the hepatitis B virus surface antigen) became the first and second approved human antiparasitic vaccines in 2021 and 2023, respectively [ 2 , 52 , 53 ]. Thus, substantive funding needs to be allocated continuously to HE institutions for research if game-changing solutions for public health challenges are to be observed on the continent.…”
Section: Research and Developmentmentioning
confidence: 99%
“…Timely advocacy for parents and communities embracing this vaccination is expedient to create awareness for integrating all 3 strategies, which could provide a more comprehensive approach, protecting children from malaria by up to 90% and emphasizing the need for a diversified strategy in combating the disease. 3 Comprehensive planning is recommended to ensure the malaria vaccine’s effective distribution in other African countries. This includes establishing a national immunization policy and recommendations, as well as smoothly incorporating the new vaccine into preexisting schedules for delivery with other vaccinations and health interventions.…”
Section: Dear Editormentioning
confidence: 99%
“…Governments should invest in innovating diagnostics to increase sensitivity and specificity, improve data quality, and train practitioners to ensure effective malaria control and immunization. 2 , 3 …”
Section: Dear Editormentioning
confidence: 99%